"GEOPHYSICAL RESEARCHES OF MINING HOLES" – 50 YEARS AT TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV - Kurgansky, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Development of carotage (retrospective years 1969-2019) at Taras Shevchenko National University of Kyiv is described. Basic achievements are shown in educational and scientific directions. Carbonate rocks methodology study problems, petrophysical models which allowed building physically well-founded dependences of "core-core", "core-geophysics", "geophysics- geophysics" type are described. Petrophysical simulation, theory of probability and mathematical statistics methods allowed the author to work out a complex system of data processing and interpretation in welllogging. Current status and tendency in dataware drilling process of the deep oil and gas wells are examined. Absolutely new ideology of operative getting of the reliable directional survey data without special logging services (telesystem in the process of drilling, autonomous inclinometer and other) is proposed.
Keywords: geophysical well-logging (carotage); petrophysic models; carbonate rocks; rocks-reservoirs; interpretation; porosity; saturation; geonavigation; telesystem in the process of drilling; autonomous inclinometer; micromechanical sensors